The relation between family socioeconomic status and depressive symptoms among children and adolescents in mainland China: a meta-analysis - Niu, Yingnan; Guo, Xiaolin; Cai, He; Luo, Liang (Frontiers in Public Health, 2024)
Family socioeconomic status (SES) is widely believed to be associated with depressive symptoms in children and adolescents. The correlation between SES and depressive symptoms changes based on social culture and the economic development level. In China, which includes many children and adolescents, the magnitude of the relationship between SES and depressive symptoms and its potential moderators remains unclear. The current meta-analysis was conducted to determine the overall association between SES and depressive symptoms in children and adolescents in mainland China. We included 197 estimates in mainland China from 2000–2023. Among 147,613 children and adolescents aged 7–18 years, the results showed a weak but significant overall negative association between SES and depression (r = −0.076). Moderator testing showed that the composite SES indicator (r = −0.104) had a stronger association with depression than parental educational level (r = −0.065) and occupational status (r = −0.025) but not family income (r = −0.088). Additionally, the negative association between SES and depression became weaker over the past 20 years in China (β = 0.010). Furthermore, the magnitude of the relationship between SES and depression was stronger in West China (r = −0.094) than in Middle China (r = −0.065), but not East China (r = −0.075). These findings indicate that the relationship between SES and depression among children and adolescents in mainland China may vary based on social contexts. It is necessary to further explore the effect of these social factors and the underlying mechanisms.